A comparative analysis of the performance of linear detectors for wireless multicasting through interference limited cognitive radio channels. (2015) - Giti, J.E.; Chowdhury, S.A.H.; Ali, M.M.
We consider the problem of wireless multicasting through multiple-input multiple-output (MIMO) cognitive radio channel in which primary and secondary users simultaneously communicate with their corresponding group of receivers instead of waiting for an idle channel as we see in the traditional cognitive radio. Using a code-division multiple-access (CDMA) technique, we evaluate the performance of minimum mean square error (MMSE) detector in multicasting application through interference limited cognitive radio channels. We also compare the performance of MMSE detector with conventional zero-forcing (ZF) and maximal-ratio-combining (MRC) detectors. Our results show that MMSE detector performs better than ZF and MRC detectors.